Unveiling the Impact of GDP, Population, Energy Consumption, and Trade Globalization on the Load Capacity Factor in Türkiye: Nonlinear Approaches - Celik, Ali; Güriş, Burak (Ekonomika, 2025)
It is clear that the climate crisis is having a profound impact on the entire ecosystem. In order to prevent it, it is essential to first identify and address its causes. This study investigates the effects of Gross Domestic Product (GDP), population, primary energy consumption and economic globalization on the Load Capacity Factor (LCF) in Türkiye over the period from 1965 to 2022 by using the Wavelet Coherence (WCO), Quantile on Quantile Regression (QQR) and Augmented Autoregressive Distributed Lag (AARDL) methods. The results of WCO showed a negative correlation between LCF and GDP, as well as primary energy consumption while a positive correlation was detected between LCF, population, and trade globalization. Moreover, QQR results indicate that GDP has a positive impact on LCF at the upper quantiles, while GDP leads to a decrease in LCF at the lower quantiles. Moreover, population and primary energy consumption have a negative impact at different quantiles, while trade globalization has a negative and positive impact on LCF at different quantiles. The AARDL test results prove that an increase in GDP worsens LCF in the long run. It has also been found that population growth increases LCF, while primary energy consumption decreases LCF in the short run. These findings highlight the complex interactions influencing LCF and underscore the need for targeted policies. Therefore, these findings are important for the roadmap that policy makers could follow in terms of the climate policy.
Keywords: Load capacity factor; nonlinear approaches; wavelet coherence; quantile on quantile; AARDL